2021
DOI: 10.1007/s43154-020-00035-0
|View full text |Cite
|
Sign up to set email alerts
|

What Makes a Robot Social? A Review of Social Robots from Science Fiction to a Home or Hospital Near You

Abstract: Purpose of Review We provide an outlook on the definitions, laboratory research, and applications of social robots, with an aim to understand what makes a robot social—in the eyes of science and the general public. Recent Findings Social robots demonstrate their potential when deployed within contexts appropriate to their form and functions. Some examples include companions for the elderly and cognitively impaired individuals, robots within educational set… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
64
0
5

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
3
1
1

Relationship

3
6

Authors

Journals

citations
Cited by 130 publications
(97 citation statements)
references
References 87 publications
1
64
0
5
Order By: Relevance
“…Studies that investigated individual differences, for example, have shown that individual differences in resting-state beta rhythms in the brain [11], experiencing loneliness [12], and expectations regarding the capabilities of robots can predict whether people would explain a robot's behavior in mentalistic or mechanistic terms [13]. Studies that investigated robot factors have shown that robots that are embodied [14], look humanlike [15], behave unexpectedly ( [10]), display variability in their behavior [16], or cheat [17], [18] are more likely to have their behaviors explained in mentalistic terms as opposed to mechanistic terms (For a review, see [19]). More recently, Lefkeli and colleagues [20], asked participants to play in cooperation with-or competition against a robot.…”
Section: Introductionmentioning
confidence: 99%
“…Studies that investigated individual differences, for example, have shown that individual differences in resting-state beta rhythms in the brain [11], experiencing loneliness [12], and expectations regarding the capabilities of robots can predict whether people would explain a robot's behavior in mentalistic or mechanistic terms [13]. Studies that investigated robot factors have shown that robots that are embodied [14], look humanlike [15], behave unexpectedly ( [10]), display variability in their behavior [16], or cheat [17], [18] are more likely to have their behaviors explained in mentalistic terms as opposed to mechanistic terms (For a review, see [19]). More recently, Lefkeli and colleagues [20], asked participants to play in cooperation with-or competition against a robot.…”
Section: Introductionmentioning
confidence: 99%
“…Social robots hold great potential for delivering or improving psycho-social interventions (65), supporting mental health (68), monitoring symptoms of chronic pathologies (47), and providing much-needed physical and social support across a number of daily life settings (34). The recent COVID-19 pandemic further illuminated the potential of social robots as an assistive technology in times when strict infection control measures mandate physical distancing between people.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, reflecting on relevant studies with other types of artificial agents and machines provides a meaningful context to the study of fallacious social robots. Social robots were previously found to have a genuine effect on people's decisions in a variety of contexts and settings (19). Social robots' influence on people's decisions is usually determined by the robot's available and related social cues, as well as people's expectations of the robot (58).…”
Section: Fallacious Artificial Agentsmentioning
confidence: 99%